Geology, geochemistry and depositional history of the Port Campbell Limestone on the eastern flank of the Otway Basin, southeastern Australia. Issue 4 (19th May 2022) - Radke, B.; Champion, D. C.; Gallagher, S. J.; Wang, L.; De Vleeschouwer, D.; Kalinowski, A.; Tenthorey, E.; Urosevic, M.; Feitz, A.
Abstract: A fully cored sequence of Hesse Clay, Port Campbell Limestone and uppermost Gellibrand Marl in the onshore Otway Basin, southeastern Australia, offers new insight into the evolution of the middle Miocene Port Campbell Limestone. The Port Campbell Limestone comprises grey unconsolidated to semi-consolidated and rarely lithified bioclastic muddy carbonate sands in a stack of thin repetitive cycles within cycles of predominantly shoaling-upward character. A glauconitic band with a distinctive mollusc–echinoderm–bryozoan fauna provides a distinctive marker interval in the sequence. In mineralogy, the Port Campbell Limestone is predominantly calcite with traces of remnant aragonite in muddier low-permeability sands, and with dolomitic zones in permeable intervals. The small non-carbonate component of the Port Campbell Limestone is between 3 and 15 wt% and comprises quartz silt with minor clay, feldspar and mica. Dissolution overprints are prominent throughout the carbonate sequence. Three distinct geochemical signatures of provenance are evident in the Port Campbell Limestone sequence, including possible volcanogenic contributions with felsic sources. Foraminifera are common and generally well preserved. Foraminiferal data suggest a depositional transition from outer shelf conditions in the Gellibrand Marl at ca 15 Ma to middle shelf environments in the lower part of the Port Campbell Limestone during the Middle Miocene Climatic Optimum (MMCO) at ca 14.24 Ma. Shallowing after 14 Ma indicates variable paleodepths of <70 m during and following the end of the Middle Miocene Climatic Transition (MMCT) at ca 13.2 Ma when the sequence was emergent for a brief but undetermined period, corresponding with sharp changes in geochemical ratios. Observed cyclicity in these mid-shelfal, cold-water carbonates is strongly correlated with orbital forcings—eccentricity and obliquity. Sedimentation rates determined from cyclostratigraphic analysis indicate 4–6 cm/kyr at the end of the MMCO, diminishing to 1.5–3 cm/kyr during the MMCT and the subsequent accumulation of the Port Campbell Limestone. KEY POINTS: The Port Campbell Limestone is a stack of thin repetitive depositional cycles within cycles. The cyclicity is strongly correlated with orbital forcings—eccentricity and obliquity—and this is reflected in the geochemistry. Foraminiferal data suggest a depositional transition from outer shelf conditions in the Gellibrand Marl at ca 15 Ma to middle shelf environments in the lower part of the Port Campbell Limestone during the Middle Miocene Climatic Optimum (MMCO) at ca 14.24 Ma. The sequence was emergent for a brief but undetermined period at ca 13.2 Ma, corresponding with sharp changes in geochemical ratios. Three distinct geochemical signatures of provenance are evident in the Port Campbell Limestone sequence, including possible volcanogenic contributions with felsic sources.